Tsunami Force on a Building With Sea Wall Protection - Any Nurhasanah; . Nizam; Radianta Triatmadja (International Conference on Engineering and Technology Development (ICETD), 2014)
The frequency of tsunami in Indonesia is increasing since the past few decades. The increasing of both the frequency of tsunami and the population in coastal area intensify the vulnerability of such area to tsunami disasters. Tsunamis do not only cause a large number of casualties but also damages to infrastructures along the shore. Wall protection is one possible solution to reduce tsunami force. The effectiveness however depends on the ratio between the tsunami height to the wall height and the distance between the wall and the buildings.A 24m long flume of 1.45m width and 1.5m height was utilized for the experiment. Various tsunami wave fronts were generated using a dam break mechanism. The model of buildings was tested both with and without wall protection installed at various distances in front of the buildings.The results indicated that the force reduction of building depends on the ratio between sea wall height and building high. A simplified formula for the calculation of tsunami force on protected building is proposed